(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2020)
Design for a Dissemunization Station (D4DS) is a collaboration between Annemarie Hou, Executive Director a.i. of the United Nations Office for Partnerships and was then a UNAIDS building-based executive and advocacy expert interested in ideas and problems surrounding accessibility and vaccines, and Patrick Mahon, a university-based artist and curator. An installation consisting of two tent structures, D4DS included listening stations and provided ambient sounds suggestive of a vaccine moving through the body. The hybrid term “dissemunization” was used to reveal ideas concerning distribution of vaccines and related information. Hou and Mahon reflect on the project and assess its success with respect to aspects of collaboration.